Pseudomonas aeruginosa MurE amide ligase: enzyme kinetics and peptide inhibitor - Paradis-Bleau,C; Lloyd,A; Sanschagrin,F; Maaroufi,H; Clarke,T; Blewett,A; Dowson,C; Roper,DI; Bugg,TDH; Levesque,RC (Biochemical Journal, 2009)
The enzyme kinetics of the amide ligase MurE, a cell wall biosynthesis enzyme, from Pseudomonas aeruginosa were determined using the synthesized nucleotide substrate UDP-MurNAc-Ala-Glu (uridine 5′-diphosphoryl N-acetylmuramoyl-L-alanyl-D-glutamate). When coupled to a competitive bio-panning technique using a M13 phage display library encoding ∼2.7×109 random peptide permutations and the specific substrates meso-A2pm (meso-diaminopimelic acid) and ATP, a peptide inhibitor of MurE was identified. The MurEp1 dodecamer selected and synthesized inhibited MurE ATPase activity with an IC50 value of 500 μM. The inhibition was shown to be time-dependent and was reversed by the addition of meso-A2pm or UDP-MurNAc-Ala-Glu during the pre-incubation step. Kinetic analysis defined MurEp1 as a mixed inhibitor against both substrates with Ki values of 160 and 80 μM respectively. MurEp1 was found to interfere in meso-A2pm and UDP-MurNAc-Ala-Glu binding necessary for amide bond formation. Modelling of Ps. aeruginosa MurE and docking of MurEp1 on the Ps. aeruginosa MurE surface indicated that MurEp1 binds at the juxtaposition of both meso-A2pm- and UDP-MurNAc-Ala-Glu-binding sites in the closed conformational state of the enzyme. Identification of the MurEp1 residues involved in MurE binding and inhibition will allow the development of a novel class of inhibitors having a novel mode of action against MurE.